Study on concentric configuration of nematic liquid crystal droplet by Landau-de Gennes theory. Issue 11 (1st September 2020) - Wu, Jinbing; Ma, He; Chen, Sibo; Zhou, Xuan; Zhang, Zhidong
ABSTRACT: On the basis of Landau-de Gennes theory, the fine structures of escaped concentric and ideal concentric configurations confined in nematic liquid crystal droplets were investigated. The escaped concentric configuration rather than the ideal concentric configuration appeared under the same conditions and parameters reported in Liq. Cryst., 45(1): 102 − 111, 2017. After increasing k 22 (twist elastic constant in Frank theory), the escaped concentric configuration transformed into the ideal concentric configuration. Within the ideal concentric configuration, we found an unexpecting order reconstruction occurred around the +1 line disclination, which has yet to be reported. In addition, the structural transitions within droplets of different radii were simulated. Graphical abstact: uf0001